A Dashboard System for Monitoring Air Pollution in Surabaya based on PM2.5 - Valentinus Roby Hananto; I Gusti Ngurah Alit Widana Putra (Universitas Airlangga, 2018)
In developing countries where population grows rapidly, air pollution has been a serious issue for the public health. Among various pollutants, ﬁne particulate matters (PM2.5) is associated with distinct serious health problems, e.g., asthma, cancer, cardiovascular and respiratory diseases. To raise the awareness of the community and decision makers in order to solve the air-pollution problem, the level of the PM2.5 index should be monitored. In this paper, we propose a dashboard system for monitoring air pollution based on PM2.5. A portable device (i.e., Edimax Airbox) was installed inside the building of Stikom Surabaya college to measure the PM2.5 level. The sensors in this device read the PM2.5 level, air temperature, and humidity level, and then it transmits the data to the cloud service. The cloud platform makes the collected data accessible through an open data API that allows our system to interact with the data in the JSON format. The data then was parsed in a web server and visualized in a dashboard system. The dashboard system provides two indicators, the live PM2.5 sensor measurement and the measurement history. The dashboard successfully visualized the indicator of air pollution index, based on PM2.5 standards by WHO and Dinas Kesehatan Indonesia (the Indonesian Department of Health). Within seven days of the study, PM2.5 level reaches the maximum value of 65 µg/m3 with the average value of 39.36 µg/m3 on July 8, 2018. This is an alarming rate given that the indoor average level threshold of PM2.5 by WHO is 25 µg/m3.